2017
DOI: 10.5539/ies.v10n6p60
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of an Interactive Training Program in Developing a Set of Non-Cognitive Skills in Students at University of Petra

Abstract: This study aimed to investigate the effectiveness of interactive training programs in developing a set of non-cognitive skills in students at the University of Petra. Furthermore, it sought to examine the impact of the sex, academic year, and university major variables on developing these skills in students who underwent the training program, as well as whether a correlation exists between the GPA of students in the experimental group and how they acquired these non-cognitive skills. The study focused on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The findings revealed that interactive programs had helped foster the non-cognitive skills empathy, growth mindset, and Grit. 5 The qualitative phase of our study signifies the importance of personal effort and deliberate practice towards achievement and better academic performance. Students with high score on Grit were more enthusiastic, regular in attendance and always ready to participate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings revealed that interactive programs had helped foster the non-cognitive skills empathy, growth mindset, and Grit. 5 The qualitative phase of our study signifies the importance of personal effort and deliberate practice towards achievement and better academic performance. Students with high score on Grit were more enthusiastic, regular in attendance and always ready to participate.…”
Section: Discussionmentioning
confidence: 99%
“…3 Moreover, access to knowledge through information technology has changed the conventional teaching methods and it is now more important to provide guidance and support to help students in their learning. 5 It is the need of an hour to teach our students the non-cognitive skills in order to meet the challenges. These skills improve the academic performance of students, and the students manage setbacks and stress in a better way.…”
Section: Introductionmentioning
confidence: 99%
“…P(X i ) is propensity score of student i which can be estimated by a probability model, shown as formula (2).…”
Section: Modelingmentioning
confidence: 99%
“…At present, the fifth-generation mobile communication technology (5G) is quietly coming together with a new generation of artificial intelligence technology, which not only accelerates generation and dissemination of knowledge [1] but also enables various demands for workers' skills in jobs rapidly updated. The superposition has accelerated the iteration of knowledge production and skill demand [2], profoundly changing and reshaping our education and teaching system.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the traditional methods of teaching have been altered by the availability of knowledge through information technology, so it is now even more crucial to offer guidance and support to students in order to aid their learning (Gheith & Aljaberi, 2017). Educating our pupils non-cognitive skills is imperative to prepare them for future problems.…”
Section: Introductionmentioning
confidence: 99%